Strain-Specific Effects of Rosiglitazone on Bone Mass, Body Composition, and Serum Insulin-Like Growth Factor-I - Ackert-Bicknell, Cheryl L. (The Endocrine Society, 2009)
Activation of peroxisome proliferator activated receptor-γ (PPARG) is required for the differentiation of marrow mesenchymal stem cell into adipocytes and is associated with the development of age-related marrow adiposity in mice. Thiazolidinediones are agonists for PPARG and have a heterogeneous effect on bone mineral density (BMD). We postulated that genetic determinants influence the skeletal response to thiazolidinediones. We examined the effects of rosiglitazone (3 mg/kg · d for 8 wk) on BMD, body composition, and serum IGF-I in adult female mice from four inbred strains. C3H/HeJ mice showed the most significant response to treatment, exhibiting decreased femoral and vertebral BMD, reduced distal femoral bone volume fraction and a decrease in serum IGF-I. In DBA/2J, there were no changes in femoral BMD or bone volume fraction, but there was a decrease in vertebral BMD. C57BL/6J mice showed increases in marrow adiposity, without associated changes in trabecular bone volume; the skeletal effects from rosiglitazone in A/J mice were minimal. No association between trabecular bone volume and marrow adiposity was found. The effect of rosiglitazone on gene expression in the femur was then examined in the C3H/HeJ and C57BL/6J strains by microarray. Increased gene expression was observed in the PPARG signaling pathway and fatty acid metabolism in both C3H/HeJ and C57BL/6J, but a significant down-regulation of genes associated with cell cycle was noted only in the C3H/HeJ strain. The divergent skeletal responses to rosiglitazone in this study suggest the existence of a strong genetic background effect.